Steps to Develop a Performance Observation Card for University of Basrah Professors Regarding Their Argumentation Skills - Khalil Hindi, Researcher. Layla; Abdul Manshed , Prof. Dr. Faisal; Taher Iskandar , Assist. Prof. Dr. Mohsen (Basra studies journal, 2026)
The current research aims to identify the availability of Argumentative skills among the professors of Arabic language departments at the Colleges of education and of Arts at the University of Basrah. The researcher choses the research sample by random method, it included (125) professors and professors. The researcher prepares a research tool, namely the observation card which consist of 13 skills, 63 paragraphs and five alternatives, and applied it to the basic research sample using the following statistical means: Pearson correlation coefficient, Alpha-krubach equation, Test (t), variance analysis test (f), standard deviation Arithmetic mean, weighted mean. The results of the research show that the research sample has a low and weakness in the skills of argumentation for the first goal, and in order to achieve the second goal, the researcher calculates the results according to the gender variable and the results showed that there are no differences between males and females in the degree of possession of argumentation skills. As for the third goal, the results show that there are no differences in the degree of possession of argumentation skills between the colleges of education and arts In light of the result of the current research, the researcher concluded a number of conclusions, including : The use of persuasive argumentative skills supports interaction and integration into the educational process, enhances the spirit of discussion, develops thinking and rises to higher mental levels. In addition to this research, the researcher proposes a number of studies, the most important of which are : Conducting experimental studies aims at revealing the most important problems facing professors in Hajj skills and developing plans and programs to solve these problems and improve the level of skills.